Role of Prostaglandin E2 Gel for Induction of Labour in Preeclamptic Patients - Banu, Jesmine; Shamsuddin, Latifa (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: prostaglandin E2 gel; induction of labour; pre-eclampsia DOI: 10.3329/jcmcta.v20i1.4928 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):12-15